Impact of digitalization of sales on the profitability of the restaurant industry during COVID-19 - Mónica González Morales; José Antonio Cavero Rubio (Economies, 2023)
The COVID-19 pandemic had a severe impact on the restaurant industry. Temporary shutdowns and seating capacity restrictions led to a sharp drop in sales. In this scenario, digitalization emerged as a crucial strategy for business survival, offering opportunities to increase restaurants' competitiveness and revenues. This study examines the financial profitability of restaurants during 2020, comparing establishments with digital sales tools to those without. Multiple linear regression results indicate that liquidity, sales growth, restaurant size, and having a website directly influenced profitability. In addition, restaurants with their own online ordering and home delivery services or associated with delivery platforms experienced lower profitability losses. These findings contribute to our understanding of the role of digitalization in the restaurant sector during the pandemic, providing valuable practical and theoretical implications for the industry in similar contexts.
Keywords: 330; restaurant sector; digitalization; home delivery; profitability